Engineered implantable vaccine platform for continuous antigen-specific immunomodulation. (February 2022) - Viswanath, Dixita Ishani; Liu, Hsuan-Chen; Capuani, Simone; Vander Pol, Robin Shae; Saunders, Shani Zakiya; Chua, Corrine Ying Xuan; Grattoni, Alessandro
Abstract: Cancer vaccines harness the host immune system to generate antigen-specific antitumor immunity for long-term tumor elimination with durable immunomodulation. Commonly investigated strategies reintroduce ex vivo autologous dendritic cells (DCs) but have limited clinical adoption due to difficulty in manufacturing, delivery and low clinical efficacy. To combat this, we designed the "NanoLymph", an implantable subcutaneous device for antigen-specific antitumor immunomodulation. The NanoLymph consists of a dual-reservoir platform for sustained release of immune stimulants via a nanoporous membrane and hydrogel-encapsulated antigens for local immune cell recruitment and activation, respectively. Here, we present the development and characterization of the NanoLymph as well as efficacy validation for immunomodulation in an immunocompetent murine model. Specifically, we established the NanoLymph biocompatibility and mechanical stability. Further, we demonstrated minimally invasive transcutaneous refilling of the drug reservoir in vivo for prolonging drug release duration. Importantly, our study demonstrated that local elution of two drugs (GMCSF and Resiquimod) generates an immune stimulatory microenvironment capable of local DC recruitment and activation and generation of antigen-specific T lymphocytes within 14 days. In summary, the NanoLymph approach can achieve in situ immunomodulation, presenting a viable strategy for therapeutic cancer vaccines.